2022
DOI: 10.1002/jcc.26832
|View full text |Cite
|
Sign up to set email alerts
|

EDA‐NOCV analysis of carbene‐borylene bonded dinitrogen complexes for deeper bonding insight: A fair comparison with a metal‐dinitrogen system

Abstract: Binding of dinitrogen (N 2 ) to a transition metal center (M) and followed by its activation under milder conditions is no longer impossible; rather, it is routinely studied in laboratories by transition metal complexes. In contrast, binding of N 2 by main group elements has been a challenge for decades, until very recently, an exotic cAAC-borylene (cAAC = cyclic alkyl(amino) carbene) species showed similar binding affinity to kinetically inert and non-polar dinitrogen (N 2 ) gas under ambient conditions. Sinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 96 publications
0
1
0
Order By: Relevance
“…By means of eqn (5), it is possible to examine these terms individually, explicitly focusing on the processes of electron density outflow and inflow from a specific fragment. 54,59 …”
Section: Methodsmentioning
confidence: 99%
“…By means of eqn (5), it is possible to examine these terms individually, explicitly focusing on the processes of electron density outflow and inflow from a specific fragment. 54,59 …”
Section: Methodsmentioning
confidence: 99%
“…Since its isolation, complex 1 has been subjected to quite a few theoretical investigations. 5,16,17 Yet, its electronic structure remains elusive to date. In fact, the original work of Braunschweig et al and the DFT-based electronic structure analysis therein can be considered as state-of-the-art in electronic structure understanding, where the authors suggested the π-back-donation being key to the bonding scenario along with σ-donation from N 2 .…”
Section: Introductionmentioning
confidence: 99%